Phosphotungstic Acid Catalyzed One Pot Synthesis of 4, 8, 8‐Trimethyl‐5‐phenyl‐5, 5a, 8, 9‐tetrahydrobenzo[b] [1, 8]Naphthyridin‐6(7H)‐one Derivatives and Their Biological Evaluation Against A549 Lung Cancer Cells. (2nd April 2018) - Makhanya, Talent Raymond; Gengan, Robert Moonsamy; Pandian, Pitchai; Chuturgoon, Anil Amichund; Tiloke, Charlette; Atar, Atha
Abstract : A facile one pot multicomponent synthesis of 1, 8‐naphthyridinone derivatives was developed using a mild and reusable phosphotungstic acid catalyst. A 2‐amino picoline, benzaldehyde derivatives and 1, 3‐dicarbonyl cyclohexane were used to synthesize 1, 8‐naphthyridinones, which was achieved by conventional heating under solvent‐free conditions. All synthesized compounds were characterized by spectral analysis and screened for anticancer activity against A549 lung cancer cells. The results from the cell viability assay showed that the synthesized compounds do have a biological effect at various concentrations on the lung cancer cells. Compounds 4F‐p‐CF3 and 4H‐VAN showed potential as an antiproliferative agent and a dose‐dependent decline in cell viability was observed. Abstract :